2006
DOI: 10.1016/j.freeradbiomed.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Systemic elevations of free radical oxidation products of arachidonic acid are associated with angiographic evidence of coronary artery disease

Abstract: Oxidant stress is widely believed to participate in cardiovascular disease pathogenesis. However, progress in defining appropriate systemic anti-oxidant targetted therapies has been hindered by uncertainty in defining clinically relevant systemic oxidant stress measures. In a case control study, 50 subjects with CAD (> 50% stenosis in one or more major coronary vessels) and 54 without CAD (< 30% stenosis in all major coronary vessels) were tested. Plasma was isolated and stored under conditions designed to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 37 publications
3
93
0
Order By: Relevance
“…In a study of human carotid atherosclerotic plaques, the concentration of HETEs was significantly higher in symptomatic plaques, as compared with asymptomatic plaques (11). In addition, higher plasma HETE concentrations were associated with CHD in two case-control studies (12,13). However, data from larger prospective studies with a more comprehensive assessment of oxylipins are currently not available.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of human carotid atherosclerotic plaques, the concentration of HETEs was significantly higher in symptomatic plaques, as compared with asymptomatic plaques (11). In addition, higher plasma HETE concentrations were associated with CHD in two case-control studies (12,13). However, data from larger prospective studies with a more comprehensive assessment of oxylipins are currently not available.…”
Section: Discussionmentioning
confidence: 99%
“…Since analysis of the NPC-affected tissue is impractical, a sensitive circulating indicator of oxidative stress may be the appropriate biomarker in this case. Circulating unsaturated lipid peroxidation products, such as HETEs and isoprostanes ( 88,89 ), and hydroxylated cholesterol metabolites ( 85 ) may serve as the proper biomarker for these purposes. Clearly, there is a dire need to better defi ne and optimize the most suitable plasma marker for oxidation status and to streamline its applicability for routine clinical use.…”
Section: Figmentioning
confidence: 99%
“…Isoprostanes, including 8-iso-PGF 2α are stable in biological fluids and easily detectable as well as not being affected by diet and modulated by endogenous antioxidants [30]. Plasma levels of 8-iso-PGF 2α have been associated with atherosclerosis and coronary artery disease as well as DMT2 [31][32][33]. In contrast to crosssectional studies where 8-iso-PGF 2α have been shown to be increased in type 2 diabetes, longitudinal studies have shown an inverse relationship between the level of 8-iso-PGF2α and risk of diabetes independent of traditional risk factors [33,34].…”
Section: Introductionmentioning
confidence: 99%